Experimental investigation on Charpy impact response of kenaf bast fibre reinforced metal laminate system - Dhar Malingam, Sivakumar; Subramaniam, Kathiravan; Ng, Lin Feng; Ali, Mohd Basri; Selamat, Mohd Zulkefli; Bapokutty, Omar; Subramonian, Sivarao (Asian Research Publishing Network (ARPN), 2018)
Natural fibre triggers the researcher's interest due to its advantage over synthetic fibres as it is inexpensive and eco-friendly. The objectives of this study is to investigate the effect of fibre length, loading and chemical treatment of kenaf bast fibre reinforced polypropylene metal laminate under Charpy impact loading. The kenaf bast fibre loading of 50wt%, 60wt% and 70wt%, fibre length of 3 cm, 6 cm and 9 cm and chemical treatment of 0% and 5% NaOH are considered. Aluminium, 5052-O is employed as the skin for the composites in this research. The composite and FML were fabricated using hot compression moulding method. Specimens were extracted from the prepared FML panels using water jet cutter and tested in accordance to ASTM E-23 using INSTRON CEAST 9050 pendulum impact tester. The results show that the alkaline treated kenaf fibre with fibre loading 70wt% and length 9 cm absorbed the highest impact energy at 157.04 kJ/m2 compared to other fibre metal laminate compositions.